Managing public debt : from diagnostics to reform implementation. (World Bank e-Library., 2007)
"This book draws insights from a joint pilot program set up by the World Bank and International Monetary Fund to design relevant reform and capacity-building programs in twelve countries. The experiences of these geographically and economically diverse countries illustrate the challenges and elements necessary to make progress in the area of public debt management."--Jacket